Hukum Pelaksanaan Salat Jumat Dua Gelombang pada Satu Masjid di Masa Pandemi Covid-19 - Mahmuddin, Ronny; Akbar, Fadhlan; Iskandar (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2020)
The condition of the corona virus pandemic (covid-19) in Indonesia has an impact on religious life for Muslims, such as Friday prayers. The government issued a regulation on Friday prayers at mosques in areas where the distribution of the prayers was controlled with a prayer distance of one meter to prevent the spread of the virus, resulting in the mosque being unable to accommodate many worshipers at a time. The purpose of this study is to describe the opinions of the scholars regarding the two waves of Friday prayer in one mosque and the Friday prayers in addition to the mosque during the Covid-19 pandemic, and also aims to respond to community questions about these two issues in order to find the right answers so that the community can perform worship calmly. This type of research is a qualitative descriptive study using a literature review method with a normative approach. The results of this study are that the scholars disagreed about the law of the two-wave Friday prayer in one mosque during the covid-19 pandemic. A strong opinion is that it is permissible to carry out two waves of Friday prayers in one mosque, due to emergency or urgent conditions such as the covid-19 pandemic conditions, with the condition that the mosque is narrow and there is no other representative place to accommodate worshipers, the number of worshipers in the second wave is as much as the number of pilgrims in the first wave, as well as getting approval or permission from the government. The implementation of this research is expected to provide theoretical and practical contributions to scientists and society in general.